2021
DOI: 10.2147/pgpm.s322463
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNAs Gene Variants as Molecular Markers for Diabetic Retinopathy Risk and Response to Anti-VEGF Therapy

Abstract: Background: Long non-coding RNAs (lncRNAs) play essential roles in molecular diagnosis and therapeutic response in several diseases. Purpose: For the first time, we aimed to evaluate the association of four lncRNAs TUG1 (rs7284767G/A), MIAT (rs1061540T/C), MALAT1 (rs3200401C/T), and SENCR (rs12420823C/T) variants with susceptibility to diabetic retinopathy (DR), disease severity, and early therapeutic response to intravitreous anti-vascular endothelial growth factor aflibercept therapy. Patients and Methods: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…The study demonstrated that the MIAT rs1061540 T/T genotype was associated with a more severe Gensini score under codominant and recessive models, although no association with disease susceptibility was observed. In agreement with our outcome, TT homozygosity of the same MIAT variant was associated with a more advanced grade of diabetic retinopathy compared with CC and TC genotypes [ 27 ]. Ishii et al conducted a large-scale association study and reported that six MIAT SNPs (i.e., rs2331291, rs2301523, exon 3 (8813), and exon 5 (11093, 11741, and 12311)) were associated with myocardial infarction (MI) risk; however, the current study polymorphism was not found to be a risk variant [ 31 ], which could support in part our finding of inability to identify an association of this variant with the disease risk.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The study demonstrated that the MIAT rs1061540 T/T genotype was associated with a more severe Gensini score under codominant and recessive models, although no association with disease susceptibility was observed. In agreement with our outcome, TT homozygosity of the same MIAT variant was associated with a more advanced grade of diabetic retinopathy compared with CC and TC genotypes [ 27 ]. Ishii et al conducted a large-scale association study and reported that six MIAT SNPs (i.e., rs2331291, rs2301523, exon 3 (8813), and exon 5 (11093, 11741, and 12311)) were associated with myocardial infarction (MI) risk; however, the current study polymorphism was not found to be a risk variant [ 31 ], which could support in part our finding of inability to identify an association of this variant with the disease risk.…”
Section: Discussionsupporting
confidence: 90%
“…Real-time polymerase chain reaction allelic discrimination was applied in a StepOne™ Real-Time PCR System (Applied Biosystems, Thermo Fisher Scientific, Foster City, CA, USA) using TaqMan assays (Assay IDs: C__30952613_10 (A/C) for PUNISHER rs12318065, C__11783392_10 (C/T) for SENCR rs12420823, C___2467719_10 (C/T) for MIAT rs1061540, C___3246069_10 (T/C) for MALAT1 rs3200401, and C__98039038_10 (A/G) for GATA6-AS1 rs73390820, Applied Biosystems). The details of PCR contents/concentrations and PCR programming were detailed in our previous work [ 27 ]. We believe that the no template control (NTC) samples used for every assay that were run on a plate were enough to ensure no contamination.…”
Section: Methodsmentioning
confidence: 99%
“…The reported findings may underscore the importance of these oxygen sensitive lncRNAs in tumour angiogenesis as this process is largely triggered by hypoxia. One of the highly expressed lncRNAs in ECs, MALAT1, functions to protect ECs from the effects of oxygen deprivation and nutrient deprivation by stimulating moderate autophagy [ 13 ]. MALAT1 is active during the initiation stage of autophagy and during autolysosomal fusion [ 13 , 14 ].…”
Section: Expression Patterns Of Lncrnas In Endothelial Cellsmentioning
confidence: 99%
“…One of the highly expressed lncRNAs in ECs, MALAT1, functions to protect ECs from the effects of oxygen deprivation and nutrient deprivation by stimulating moderate autophagy [ 13 ]. MALAT1 is active during the initiation stage of autophagy and during autolysosomal fusion [ 13 , 14 ]. Autophagy is a process of cellular degradation in response to various stresses such as nutrient deprivation and it plays an important role in the maintenance of homeostasis.…”
Section: Expression Patterns Of Lncrnas In Endothelial Cellsmentioning
confidence: 99%
See 1 more Smart Citation